2006
DOI: 10.2113/gsecongeo.101.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Regional Surficial Geochemistry of the Northern Great Basin

Abstract: The regional distribution of arsenic and 20 other elements in stream-sediment samples in northern Nevada and southeastern Oregon was studied in order to gain new insights about the geologic framework and patterns of hydrothermal mineralization in the area. Data were used from 10,261 samples that were originally collected during the National Uranium Resource Evaluation (NURE) Hydrogeochemical and Stream Sediment Reconnaissance (HSSR) program in the 1970s. The data are available as U.S. Geological Survey Open-Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Another recommended, broader-scale method would be conventional stream sediment sampling (e.g., Ludington et al, 2006). In addition to sampling the sediment in the active channel, the authors found that sampling of vegetation within drainages and sampling stream drainage soils within the drainage depression but outside the active channel are potentially effective broader scale methods.…”
Section: Key Findings and Recommendationsmentioning
confidence: 99%
“…Another recommended, broader-scale method would be conventional stream sediment sampling (e.g., Ludington et al, 2006). In addition to sampling the sediment in the active channel, the authors found that sampling of vegetation within drainages and sampling stream drainage soils within the drainage depression but outside the active channel are potentially effective broader scale methods.…”
Section: Key Findings and Recommendationsmentioning
confidence: 99%
“…Numerous geochemical studies have been conducted at a regional level, among them Ludington et al (2006) in the U.S. northern Great Basin, Zumlot, Goodell, and Howari (2009) in New Mexico, and Lapworth et al (2012) in Nigeria. Other studies have concentrated instead in a smaller area; for example, the characterization of mineralized areas in northeast Algeria (Bounessah & Atkin, 2003) and Catorce-Matehuala in northern Mexico (Chiprés et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%